Pharmacological interactions between brivaracetam and ethanol in healthy males. (July 2017) - Kruithof, Annelieke C; Watanabe, Shikiko; Peeters, Pierre AM; de Kam, Marieke L; Zuiker, Rob GJA; Stevens, Jasper; van Gerven, Joop MA; Stockis, Armel
This double-blind, randomized, three-way crossover study explored the potential pharmacokinetic and pharmacodynamic interactions between ethanol and brivaracetam in 18 healthy males, as required for the development of CNS-active drugs. Subjects received (A) ethanol+brivaracetam, (B) ethanol placebo+brivaracetam and (C) ethanol+brivaracetam placebo. Ethanol was infused as a 5.5-hour intravenous clamp with the first 0.5-hour as loading phase to a target level of 0.6 g/L, and brivaracetam was orally administered as a single 200 mg dose. No relevant pharmacokinetic interactions were observed. Co-administration of brivaracetam and ethanol resulted in decreased saccadic peak velocity, smooth pursuit, adaptive tracking and VAS alertness, and increased body sway, saccadic reaction time and VAS score for ethanol effect compared with brivaracetam alone or ethanol alone. Additionally, the immediate word recall scores were generally lower when brivaracetam was co-administered with ethanol, whereas the delayed word test did not show clear additional effects. A post-hoc exploratory analysis for supra-additivity suggested that most pharmacodynamic effects were likely to be additive in nature, except for adaptive tracking, which appeared to be slightly supra-additive. In conclusion, brivaracetam increased ethanol effects on psychomotor function, attention and memory in healthy males. Intake of brivaracetam with alcohol is not recommended.